Differences in East Asian summer monsoon responses to Asian aerosol forcing under different emission inventories - Chen-Se Wang; Zhi-Li Wang; Ya-Dong Lei; Hua Zhang; Hui-Zheng Che; Xiao-Ye Zhang (Advances in Climate Change Research, 2022)
Opposite anthropogenic aerosol emission trends in Asia can lead to different responses of the climate. Here, we examined the responses of the East Asian summer monsoon (EASM) to changes in Asian anthropogenic aerosol emissions during 2006–2014 using a global aerosol/atmospheric chemistry–climate coupled model (BCC_AGCM2.0_CUACE/Aero) with two sets of emission inventories: the Community Emissions Data System (CEDS) inventory adopted by the Coupled Model Intercomparison Project Phase 6 (CMIP6) and the inventory developed at Peking University (PKU). The changes in Asian anthropogenic aerosol emissions during 2006–2014 between the two inventories were remarkably different, particularly in eastern China where completely opposite trends were observed (i.e., increase in the CEDS inventory, but significant reduction in the PKU inventory). The perturbation simulations with the Asian anthropogenic aerosol forcing from the two inventories showed opposite changes in aerosol optical depth, aerosol effective radiative forcing, cloud liquid water path, and total cloud cover in eastern China. The simulated ‘dipole-type’ changes (i.e., increase in India but decrease in China) in Asian aerosols and the resulting changes in local radiation budget under the PKU inventory were consistent with the corresponding observations. The summer surface temperatures over eastern China decreased by 0–0.4 K because of the Asian anthropogenic aerosol forcing under the CEDS inventory, while they increased by 0.1–0.8 K under the PKU inventory. The weakening of the EASM index caused by the Asian aerosol forcing under the PKU inventory was twofold greater than that under the CEDS inventory (−0.4 vs. −0.2). The Asian ‘dipole-type’ aerosol forcing contributed to the observed summer ‘southern drought and northern flood’ phenomenon in eastern China during 2006–2014. The slow ocean-mediated response to the regional ‘dipole-type’ aerosol forcing dominated the weakening of the EASM circulation and the precipitation changes in eastern China in the total response. This study further confirms that the biases in anthropogenic aerosol emissions over Asia can affect the CMIP6-based regional climate attribution.